1981
DOI: 10.3109/03009748109095297
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ketoprofen in Patients with Chronic Renal Failure

Abstract: The pharmacokinetics of ketoprofen were studied in 7 volunteers and in 5 patients suffering from varying degrees of renal insufficiency. All the subjects received a single oral dose (50 mg) of ketoprofen. Plasma concentrations were measured up to 24 hours after administration and urinary excretion for 2 days. Ketoprofen concentrations were determined by mass-fragmentography with a minimum level of detection of 0.02 mg/l. As expected, a reduction of the [51Cr]EDTA clearance was correlated with an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 1 publication
1
7
1
Order By: Relevance
“…Urine collections were not extended beyond 24 h after dosing since most of the aglycone and metabolites recovered were found in the initial 0-5 h aliquot with only 14% in the remainder (mean result from the five patients with the lowest CLCR). In addition, a previous study examining the disposition of tritiated ketoprofen in elderly subjects found negligible urinary excretion of radioactivity after 24 h [38], and a study of ketoprofen in patients with chronic renal failure also demonstrated negligible excretion of drug aglycone or conjugate beyond 24 h [8]. This and other studies [30,35], together with our data show considerably less urinary recovery of unconjugated and conjugated ketoprofen in the elderly compared with young healthy subjects [7,39].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Urine collections were not extended beyond 24 h after dosing since most of the aglycone and metabolites recovered were found in the initial 0-5 h aliquot with only 14% in the remainder (mean result from the five patients with the lowest CLCR). In addition, a previous study examining the disposition of tritiated ketoprofen in elderly subjects found negligible urinary excretion of radioactivity after 24 h [38], and a study of ketoprofen in patients with chronic renal failure also demonstrated negligible excretion of drug aglycone or conjugate beyond 24 h [8]. This and other studies [30,35], together with our data show considerably less urinary recovery of unconjugated and conjugated ketoprofen in the elderly compared with young healthy subjects [7,39].…”
Section: Discussionsupporting
confidence: 54%
“…A low percentage of the dose of such drugs is cleared renally in unchanged form yet, paradoxically, a number of them have diminished clearance in patients with renal dysfunction, or in elderly patients in whom renal function is reduced [8][9][10][11][12][13][14]. Moreover, coadministration of probenecid has caused a decrease in the plasma clearance of these NSAIDs [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma ketoprofen concentrations decreased from the peak with an apparent half-life of about 8.5 h which was not significantly different from the reported terminal half-life in young volunteers (8.3 h). These values which reflect release of drug from the dosage form are considerably longer than the elimination half-life (circa 2 h) of conventionally formulated ketoprofen in volunteers (Lewellen & Templeton, 1976;Stafanger et al, 1981) and elderly patients (Advenier et al, 1983). In one patient (5) on day 1, drug concentrations fell only very slowly from the peak at 5 h. However at times greater than 24 h plasma concentrations will fall more rapidly as drug delivery terminates, so that drug accumulation is not a problem.…”
Section: Resultsmentioning
confidence: 99%
“…In such a cycle the renal excretion of the acylglucuronides, which are major metabolites of the latter compounds, is decreased leading to increased plasma concentrations of conjugated drug which is then hydrolyzed to regenerate the parent compound. The futile cycle may therefore explain the decreased clearance of benoxaprofen (Aronoff et al, 1982), ketoprofen (Stafanger et al, 1981), and naproxen (Anttila et al, 1980), in patients with renal impairment. For the latter drugs, acyl-glucuronide formation constitutes a major pathway of elimination (Aronoff et al, 1982;Delbarre et al, 1976;Upton et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, elimination of such drugs was considered to be insensitive to changes in renal function (Fabre & Balant, 1976) but more recently a number of exceptions to this expectation have been documented. For example, clearance of ketoprofen (Stafanger et al, 1981), benoxaprofen (Aronoff et al, 1982), and naproxen (Anttila et al, 1980), all of which are arylpropionic acids eliminated primarily by metabolism, is reduced in patients with renal impairment.…”
Section: Introductionmentioning
confidence: 99%